Male genital morphology influences paternity success in the millipede Antichiropus variabilis - Wojcieszek, Janine M.; Simmons, Leigh W. (Behavioral ecology and sociobiology, 2011)
The genitalia of internally fertilizing animals are among the most diverse of all sexual characters. It is currently argued that genitalia evolve rapidly and divergently due to intense post-copulatory sexual selection. If true, male genital morphology should be subject to directional selection, whereby males with particular genital morphologies achieve greater paternity success. There is mounting evidence that male genital morphology can influence competitive fertilization success; however, the form of selection acting on genitalia has rarely been explored. We conducted competitive fertilization experiments using Antichiropus variabilis millipedes. Using microsatellite loci, we determined the paternity of offspring following double matings. The last male to mate had a significant paternity advantage. While no aspect of the behavior of last males was correlated with paternity success, variation in genital morphology did account for variation in last male paternity. Male genitalia were subject to nonlinear selection, with both convex (stabilizing) selection and concave (disruptive) selection acting on genital shape. This is the first study to provide evidence for sperm precedence in a millipede and only the second to document the form of post-copulatory sexual selection operating on male genital morphology. We discuss the implications of our results for the evolution of genitalia in A. variabilis and, more broadly, how our findings relate to alternative theories of genital evolution.